Needs and preferences of informal caregivers regarding outpatient care for the elderly: a systematic literature review - Plöthner, M. (BMC Geriatr, 2019)
BACKGROUND: Informal caregivers are an essential pillar for ensuring and maintaining the outpatient care of the frail elderly. Due to demographic changes, including an increase in the number of people in need of care as well as changing social structures (full-time employment of women, increasing number of single households, etc.) these informal care structures are fraught by considerable challenges. To support and facilitate informal caregivers in their role of nursing, it is important to identify their preferences, needs, and thus create a preference-oriented system. METHODS: A systematic review was conducted to identify preferences and needs regarding the organization of informal care. The database searches were performed by using EMBASE, Scopus and Dimdi. RESULTS: A total of 44 studies were included in the present review. Studies from 17 different countries provide broad international perspectives. Besides the preferences for long-term care structure, the following four principal topics were identified: (1) informational needs; (2) support needs; (3) organizational needs, and (4) needs for societal recognition. CONCLUSION: To meet the current challenges in the outpatient or home-based care of elders, it is essential to strengthen the role of informal caregivers. Therefore, it is necessary to adopt and further develop informal care structures according to the needs of informal caregivers. However, demographic, financial and cultural aspects of each country need to be considered as these may influence the preferences and needs of informal caregivers.